Analisis Kuantitatif Penggunaan Antibiotik pada Pasien Infeksi Saluran Pernapasan Akut Menggunakan Metode ATC/DDD dan DU90% di Puskesmas Bulango Kabupaten Bone Bolango Periode Januari–Desember 2025 - Mohamad Rizaldy Hiola; Misgiati Misgiati; Nanang Ardianto; Prisca Safriani Wicita (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
settings and a major driver of antimicrobial resistance (AMR). This study aimed to evaluate the quantitative pattern of antibiotic use in ARTI patients at Bulango Health Center, Bone Bolango Regency, during January–December 2025, using the Anatomical Therapeutic Chemical/Defined Daily Dose (ATC/DDD) and Drug Utilization 90% (DU90%) methods. A descriptive observational retrospective study was conducted on 179 samples using the ATC/DDD and DU90% methods. Five antibiotics were identified: cefadroxil (J01DB05), amoxicillin (J01CA04), cotrimoxazole (J01EE01), ciprofloxacin (J01MA02), and metronidazole (P01AB01). Total antibiotic consumption was 356.7 DDD. Cefadroxil had the highest consumption at 210.9 DDD (3.23 DDD/1000 patient-days; 59.13%), followed by amoxicillin at 132.2 DDD (2.02 DDD/1000 patient-days; 37.06%). DU90% analysis identified cefadroxil and amoxicillin as the antibiotics within the DU90% segment, with a cumulative percentage of 96.2%. Cefadroxil dominance over amoxicillin is inconsistent with national therapeutic guidelines recommending amoxicillin as first-line therapy for ARTI. These findings emphasize the need for an Antimicrobial Stewardship Program (ASP) at the primary health care level